Commentary on the United Nations Convention on the Rights of the Child, Article 37: Prohibition of torture, death penalty, life imprisonment, and deprivation of liberty - Schabas, William (Nijhoff eBook titles 2006, 2006)
Preliminary Material /André Alen , Johan Vande Lanotte , Eugeen Verhellen , Fiona Ang , Eva Berghmans and Mieke Verheyde -- Chapter One. Introduction /André Alen , Johan Vande Lanotte , Eugeen Verhellen , Fiona Ang , Eva Berghmans and Mieke Verheyde -- Chapter Two. Comparison with Related International Human Rights Provisions /André Alen , Johan Vande Lanotte , Eugeen Verhellen , Fiona Ang , Eva Berghmans and Mieke Verheyde -- Chapter Three. Scope of Article 37(a) /André Alen , Johan Vande Lanotte , Eugeen Verhellen , Fiona Ang , Eva Berghmans and Mieke Verheyde -- Chapter One. Introduction /André Alen , Johan Vande Lanotte , Eugeen Verhellen , Fiona Ang , Eva Berghmans and Mieke Verheyde -- Chapter Two. Comparison with Related International Human Rights Provisions /André Alen , Johan Vande Lanotte , Eugeen Verhellen , Fiona Ang , Eva Berghmans and Mieke Verheyde -- Chapter Three. Scope of Article 37(B), (C), (D) /André Alen , Johan Vande Lanotte , Eugeen Verhellen , Fiona Ang , Eva Berghmans and Mieke Verheyde.